(untitled) (Web of Teachers: Inderscience Research, 2025)
This study examines the formation and development of students’ cognitive competencies in digital education. With the rapid advancement of digital technologies, the integration of e-learning tools into educational processes has become essential. The research investigates methods, models, and pedagogical interventions that enhance students’ ability to acquire, process, and apply knowledge effectively. The results demonstrate that targeted e-learning strategies significantly improve cognitive competencies, fostering critical thinking, creativity, and independent learning skills. Recommendations for effective implementation in higher education are discussed.